QUALITY EDUCATION IN A CORRUPT UNIVERSITY SYSTEM IN NIGERIA - Isaac Jacobs, Aristotle; G. Ibani, Bubarayi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the quality of university education within the context of systemic corruption in Nigerian higher education institutions. Method: Using a conceptual and literature-based approach, the paper explores key themes including the definition of quality education, manifestations of corruption, and the typology of corrupt practices in Nigerian universities. It further analyzes challenges confronting the system such as inadequate funding, shortage of qualified personnel, poor infrastructure, and limited ICT resources. Results: The findings reveal that corruption—coupled with increasing demand for university education—significantly impairs institutional effectiveness, reduces academic standards, and undermines public trust. Key barriers to quality include insufficient financial support, weak quality assurance mechanisms, and politicization of university leadership. Novelty: This paper contributes to the discourse by linking systemic corruption directly to quality degradation in Nigerian universities and by offering actionable recommendations such as policy reform, depoliticization of leadership roles, improved funding, institutionalization of quality assurance practices, and strict sanctions against corrupt actors. These insights provide a roadmap for restoring integrity and enhancing educational outcomes in Nigeria’s higher education sector.